Biomechanics of the Brain - Miller, Karol; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
The mechanical properties of living tissues continue to be the major topic of biomechanical investigations. Most researchers have investigated load-bearing tissues, such as bones, ligaments, muscles and other components of the musculoskeletal system, blood vessels (and blood), lungs, skin and hair. Until recently, very soft tissues of organs whose role has little or nothing to do with transmitting mechanical loads have been outside the scope of the mainstream biomechanical research. These (3z(Bneglected(3y (Borgans include the liver, kidneys, prostate and other abdominal organs, and especially the brain. Increased interest in the biomechanics of soft tissues, particularly the brain, as evidenced by the increased number of publications in this area, has motivated this effort to summarize recent developments. Biomechanics of the Brain will take the reader to the forefront of current research. Covering topics from brain anatomy and imaging to sophisticated methods of modeling brain injury and neurosurgery, to the cutting edge methods in analyzing cerebrospinal fluid and blood flow, this book is the first comprehensive reference in the field of biomechanics of the brain. Experienced biomechanics researchers as well as those new to the field will find parts of this book useful.s
Introduction -- Introduction to Brain Anatomy -- Introduction to Brain Imaging -- Brain Tissue Mechanical Properties -- Modeling of the Brain for Injury Simulation and Prevention -- Biomechanical Modeling of the Brain for Computer-Assisted Neurosurgery -- Dynamics of Cerebrospinal Fluid From Theoretical Models to Clinical Applications -- Computational Fluid Dynamics for the Assessment of Cerebrospinal Fluid Flow and Its Coupling with Cerebral Blood Flow -- Algorithms for Computational Biomechanics of the Brain.
Keywords: Physics; Neurosurgery; Biomedical engineering; Physics; Biophysics and Biological Physics; Biomedical Engineering; Neurosurgery